Antonio Gramsci e a educação de trabalhadores: um estudo de tradutibilidade e filologia a partir dos escritos jornalísticos - Maia, Júlio César Apolinário (2024)
The present thesis, defended within the research line “Work, Education, and Social Movements”, of the Post-graduate Program in Education of the Public University of Goiás, is dedicated to deepening the theoretical-methodological contribution of Antonio Gramsci, based on criteria of translatability and philology, to the reflection on the education of workers. The bibliography and documents consulted are focused on the period of Gramsci’s life preceding his prison imprisonment. Therefore, biographical studies, journalistic writings, letters, and testimonies from those who experienced firsthand or had contact with Gramsci constitute the investigative corpus of the research. The reading and interpretation of Gramsci’s life are theoretically and methodologically based on the concepts of translatability and philology, presented in the first chapter of the thesis, which identify him as an antagonistic stance, grounded in the progressive development of a confrontation against any deterministic form of reason detrimental to the working class. The worldview of Gramsci is subject to interpretations that imply the assertion of new and exclusive actions on reality. From this argument, his conceptions of education and the education of workers, as well as those of his interpreters, are investigated. The movement of reading and action, interpretation and application, or even theory and practice, expressed in journalistic writings, analyzed in the following two chapters, strives to apprehend the theme of education of workers in Gramsci’s perception, based on the characteristics of synchrony and diachrony. Writings from two periods of journalistic production are analyzed, the first from 1914 to February 1919 and the second from April 1919 to November 1926, associated with the movements of ascent of a revolutionary project and another of resistance, respectively alluding to what the thesis terms as the “revealed alternative” and the “possible alternative” for the education of the working classes. The thesis highlights the implications of the pedagogical and political path outlined by Gramsci’s experiences for the education of workers and the pedagogical and political propositions derived from the selected writings. Among the implications and propositions, it is essential to highlight, primarily, the imperative of this education to be, as it always was for Gramsci, in line with the interests of the working classes; also, the importance of this education advancing beyond a propaedeutic conception, abandoning the exclusivity of a pedagogical orientation to learning, and replacing it, in the Gramscian manner, with its combination with the moral formation of the individual; also the affirmation of listening and dialogue, in contrast to a linear process of teaching and learning, which enables the expansion of the relationship between teacher and student; and the perception of places of practice, conductors of distinct, but equally important, pedagogical initiatives, sometimes combined with Gramsci’s notion of “evangelical propaganda” work, sometimes with the notion of creative work.